The Relationship between Family Support and Quality of Life among the Elderly in Malingping Hamlet, Sukahati Village, Bogor - Ziska Herawaty; Nipsyah Lega; Wahyu Budi Setiawati (International Journal Of Health Science, 2025)
The elderly experience an aging process that causes physical, psychosocial, and spiritual changes. These changes affect the quality of life of the elderly. Family support is one of the most essential factors in improving the quality of life among the elderly. This study employed a correlational descriptive design with a cross-sectional approach. The population in this study consisted of all elderly patients in Sukahati Village, Bogor, totaling 56 individuals. The sampling technique used was purposive sampling. Two questionnaires were applied as research instruments: the Perceived Social Support Family Scale (PSS-Fa) to measure family support, and the WHOQOL-BREF questionnaire to assess quality of life. Statistical analysis was performed using the chi-square test. The results of this study show that the chi-square test revealed 87.5% of respondents received good family support, and 53.58% had a good quality of life. The chi-square test yielded a p-value of 0.00, which is less than the α level of 0.05. A significant relationship was found between family support and the quality of life of the elderly in Sukahati Village, Bogor.